REPRESENTATION OF LOCAL WISDOM AND CULTURAL IDENTITY IN PRIMARY SCHOOL ENGLISH TEXTBOOKS - Neng Ana Aprilya Nupus; Muhammad Syafiq Gumilang (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2026)
The present study examines how English primary school textbooks in Indonesia represent cultural identity and local wisdom within the pedagogical paradigm of the Indonesian Kurikulum Merdeka, employing Cortazzi and Jin's (1999) cultural categories. The study focuses on critically analyzing the textual and visual representations of Source, Target, and International Cultures as found in the Grow with English series used by Grade 1 and Grade 5 learners at Raudhatul Jannah Elementary School. The research methodology, based on sociolinguistic theory, utilizes a qualitative Critical Content Analysis which triangulates textual and visual document analysis with semi-structured interviews with a homeroom teacher as well as practical pedagogical resonance. The findings illustrate unmistakable Source Culture orientations evidenced from local geographic nomenclatures, national school uniformations, and less controversial symbols with regional and religious associations (the hijab, the udeng), pervasive among the Target Cultures or International Cultures. However, the textbooks cater to Indonesian national policy (Permendikbudristek No 12 of 2024) and local ordinances (Cilegon Mayor's Regulation) and lead English teaching in strictly localized sociolinguistics contexts immediately relatable to students. The study ends with this, which says that their model of localized content will bring down the set of effects filters, called sociolinguistic dissonance and builds a local id, indigenously infused ready for global bilingual identity.